Simulation of multiwave pumped fiber Raman amplifiers - Felinskyi, G.S.; Korotkov, P.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The design model for development of optical fiber Raman amplifiers with the multiwavelength pumping scheme is proposed in this work. Our simulation based on the oscillator theory and spectroscopic model for the analysis of the Raman gain spectrum. Introducing the oscillatory lineshape functions gives the possibility for simple describing the wavelength dependence of Raman gain in optical fibers and it is very useful for the estimation of the gain bandwidth, Raman laser conditions, noise perfomance, and amplification processes in the Raman amplifiers. Modeling results are obtained without traditional solving the complicated system of coupled equations. The concept of an actual band based on the lineshape function is useful for the design of fiber Raman amplifiers with multiple wavelength pumping. Model validity is confirmed by the experimental measurements of amplified spontaneous emission in silica fiber. Proposed modeling allows us to analyze the fiber Raman amplifier with combined multiwavelength pumping source for the extension of amplification bandwidth to L-band, which has the broad bandwidth over 80 nm and low gain ripple less than 0.5 dB. The proposed spectroscopic model can be further extended for the analysis of the complex spontaneous Raman scattering spectra with other doping materials.